Planning for the future: Incorporating global and local data to prioritize coral reef conservation. (September 2017) - Harris, Jill L.; Estradivari, E.; Fox, Helen E.; McCarthy, Orion S.; Ahmadia, Gabby N.
Abstract: It is necessary, yet challenging, to manage coral reefs to simultaneously address a suite of global and local stressors that act over the short and long term. Therefore, managers need practical guidance on prioritizing the locations and types of conservation that most efficiently address their goals using limited resources. This study is one of the first examples of a vulnerability assessment for coral reefs that uses downscaled global climate change projections and local anthropogenic stress data to prioritize coral reef locations for conservation investment. Vulnerability was separated into manageable and unmanageable components (bleaching likelihood and local anthropogenic stressors, respectively), and the highest priority was given to places with low levels of unmanageable threats and high levels of manageable threats. Following prioritization, resilience characteristics were derived from standard reef monitoring data and used to identify the specific conservation strategies most likely to succeed given local ecological conditions and threats. Using Indonesian coral reefs as a case study, 9.1% of total coral reef area was identified as of high conservation priority, including parts of Raja Ampat, Sulawesi, and Sumatra that are not currently included in marine protected areas (MPAs). Existing MPAs tend to be located in areas less threatened by local‐scale anthropogenic activities, which has implications for both the implementation costs and the likely impact of conservation investment. This approach employs common and publicly available data and can therefore be replicated wherever managers face the familiar challenge of allocating limited conservation resources in the face of rapid global change and uncertainty.